«Our military organization ... continues to consider you as leader»: the letter and report to General M. V. Alekseev about the white underground in Kazan and Tsaritsyn. 1918 - A. V. Ganin (Омский научный вестник: Серия "Общество. История. Современность")
The readers are invited to publish a letter and a report to the leader of the White movement in the South of Russia, General M.V. Alekseev about the white underground in Kazan and Tsaritsyn in 1918. The author of the letter, General Yu.D. Romanovsky, led an underground anti-Bolshevik organization in Kazan. The documents deal with a wide range of significant issues: the activities of the antiBolshevik underground in the Volga, relations between different factions within the anti-Bolshevik camp, and white relations with French representatives